Developments in the European market of organic agricultural products - Ioan-Niculae Alecu; Anda-Irina Angelescu; Alina Mărcuţă; Carmen Angelescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
This paper represents an analysis of the development of the European organic agricultural product market, taking into account especially the consumption of organic agricultural products and some aspects regarding the consumers' behaviour. The period between 2000 and 2012 was analysed, with particular attention to the situation existent in 2012 and with references to the global situation. The tendencies that are foreseen for the future of this market segment are also considered. The conclusions of this analysis emphasize the idea that, in an era when the population is increasingly more informed and interested in its health and of the environment it is living in, the organic food market, which is still a niche market, has real opportunities of development. The only condition is that all of those involved in this sector of organic farming (producers, processors and retailers) join forces in order to develop concepts and strategies for the organic farming of the future.
Keywords: 330; Consumption; organic product market; distribution channels